PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN GAMBAR TEKNIK DI SMK NEGERI 3 KUNINGAN - Nita Kurnia Dewi, - (2020)
The background of this study comes from the students' learning problems, specifically, students' learning motivation which can affect the learning outcomes in engineering drawing subject at SMK Negeri 3 Kuningan. The main issue of this study is the low value of understanding the material regarding the technical drawings so that most of the students' scores do not meet the minimum graduation requirements (KKM). The purpose of this study in general was to determine the influence of learning motivation on students' learning outcomes in engineering drawing subjects at SMK Negeri 3 Kuningan. The method used in this study is the expost facto method with correlational approach. The research subjects were 46 students of class X DPIB at SMK Negeri 3 Kuningan. The data techniques used were questionnaire. The research instruments are in the form of questionnaires. The learning outcome in this study was obtained from the objective tests that have been tested by assessment experts, validity and reliability tests. The data analysis was performed using data normality test, correlation test, determination coefficient test and hypothesis testing. The results of this research is that students' learning motivation is in the high category, most of the students' learning outcomes still do not meet the KKM or are categorized as sufficient. In this study, it shows that learning motivation has a positive effect on student learning outcomes in engineering drawing subjects at SMK Negeri 3 Kuningan.